2, 2′-(Arylenedivinylene)bis-8-hydroxyquinolines exhibiting aromatic π–π stacking interactions as solution-processable p-type organic semiconductors for high-performance organic field effect transistors. Issue 14 (8th June 2021) - Sehlangia, Suman; Sharma, Shivani; Sharma, Satinder K.; Pradeep, Chullikkattil P.
Abstract : A new class of solution-processable small molecule organic semiconductors that are capable of functioning at low operating voltages (∼6 V) have been developed and their structure–activity correlation has been studied using crystallographic analyses. Abstract : Solution-processable organic semiconductors capable of functioning at low operating voltages (∼5 V) are in demand for organic field-effect transistor (OFET) applications. Exploration of new classes of compounds as organic thin-film transistor (OTFT) materials is an emerging research area. In this paper, a new series of π-conjugated oligomeric compounds, 2, 2′-(arylenedivinylene)bis-8-hydroxyquinolines, has been explored as solution-processable organic semiconductor materials for low voltage OFET application for the first time. Crystal structure as well as Hirshfeld surface analyses of one of the compounds revealed the existence of strong face-to-face π–π stacking interactions among the molecules leading to the infinite chain-like arrangements in the crystal lattice. These π–π stacking interactions are further supported by several O–H⋯O, C–H⋯O and C–H⋯S interactions as well. In the slipped face-to-face π–π stacking interactions exhibited by these molecules, the inter-planar distances were in the range 3.491–3.5262 Å, while the slippage angles were in the range 18.8–20.4°. This class of compounds is soluble in common organic solvents such as tetrahydrofuran (THF), which ensures their solution processability. The semiconducting properties of these compounds were established by fabricating OFET structures using polymethylmethacrylate (PMMA) as the dielectric material. The transfer and output characteristics revealed p-type semiconducting behavior exhibiting considerable high field-effect hole mobilities of ∼1.28 cm 2 V −1 s −1 at low operating voltages (<6 V) and a considerable I on/off ratio of 10 3 at 75 °C. These results successfully demonstrated the potential candidature of 2, 2′-(arylenedivinylene)bis-8-hydroxyquinoline derivatives for high-performance OFET applications.